The molecular diagnosis of Pneumocystis pneumonia in children using nasopharyngeal aspirate samples - Samuel, Catherine Mary (Division of Medical Microbiology, 2015)
Pneumocystis pneumonia (PCP) is an important opportunistic infection caused by thefungus Pneumocystis jirovecii. The incidence of PCP in sub-Saharan Africa is on theincrease. This is due to the progression of the HIV-pandemic and limited access to healthcare facilities, specific highly active anti-retroviral therapy and chemoprophylaxis. It is a major cause of hospitalization and mortality in HIV-infected children with in-hospital case-fatality rates ranging from 20-63%.